Kajian Morfologis Kompositum Semisenyawa Dan Tidak Senyawa Pada Kumpulan Puisi Karya Kahlil Gibran - Ayu Puspitasari; Aries Setia Nugraha (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
Morphology is one of the linguistic sciences that discusses the ins and outs of word formation such as compositum. Compositum is a combination of two words but the elements of compositum can be two or more words. Compositum has a word component as its forming element which has a special pattern so that it is different from other word combinations, such as idioms and phrases. The difference can be seen in terms of the level of meaning. Compositum can be classified into several types, namely based on the cohesiveness of meaning, the type of words of the elements, the distribution system, the complexity, and the language origin of the elements. Based on the cohesiveness of meaning, compositum consists of semicompound and non-compound compositum. Semicompound compositum is a compound word whose meaning is still related to the meaning of one of its elements. Meanwhile, a non-compound (tenuous) compositum is a compound word whose meaning is still related to the meaning of all its elements. Thus, many readers still do not know how semicompound and uncompound composites can be formed in Kahlil Gibran's poetry collection. In learning, there are still many educators who have not conveyed about compositum so that students do not know and have difficulty in determining compositum. Descriptive qualitative is the method used in this research. The purpose of this research is to analyze and describe semi-compound and non-compound compositum in a collection of poems by Kahlil Gibran. Based on the results of the analysis, there are 33 data including compositum based on the unity of meaning, namely 11 data showing semicompound compositum and 22 data including non-compound compositum.